Rational redesigning the Acinetobacter haemolyticus lipase KV1 for improved polyethylene terephthalate degradation via molecular docking and dynamics simulations - Khairul Anuar, Nurul Fatin Syamimi; Abdul Wahab, Roswanira; Huyop, Fahrul; Normi, Yahaya M.; Susanti, Evi; Jumbri, Khairulazhar (Taylor and Francis, 2025)
Polyethylene terephthalate (PET) is highly resistant to biodegradation, posing significant environmental risks. Fortunately, enzymatic degradation of PET offers a sustainable and eco-friendly approach to mitigating this waste, requiring a deeper understanding of the enzymatic PET hydrolysis’ binding modes and molecular mechanisms. This study evaluated the efficiency of lipase KV1 (LipKV1) variants in enhancing PET degradation through a comprehensive computational approach. Docking results revealed that variants Var9_PET (−6.2 kcal/mol), Var18_PET (−6.0 kcal/mol), and Var181_PET (−6.0 kcal/mol) exhibited higher binding affinities than the wild-type (-2.5 kcal/mol). Molecular dynamics simulations highlighted their remarkable stability and flexibility, supported by consistent RMSD (0.30 − 0.35 nm) and RMSF values (0.05 − 0.32 nm). Favorable Rg values (1.79 − 1.82 nm) also pointed to their compact and stable protein folding, while the SASA results showed reduced solvent exposure in the variants. The PET was tightly anchored within their hydrophobic active sites, with hydrogen bond distances remaining close to ∼0.25 nm. Var18 displayed the highest hydrogen bond occupancy for the key residue Ala216 (9.75%) than the wild-type (catalytic Ser165, 2.84%). Principal Component Analysis further revealed enhanced flexibility and dynamic motion in the lipase variants, suggesting improved adaptability for PET hydrolysis. These observations corresponded with the MM-PBSA results, showing marginally lower binding free energies for Var18_PET (−31.47 ± 0.54 kcal/mol) and Var181_PET (−31.58 ± 2.71 kcal/mol) than the wild-type (−29.24 ± 1.14 kcal/mol). Conclusively, the in silico findings underscore the LipKV1 variants’ enhanced PET-binding affinity for microplastic degradation, warranting further experimental effectiveness validation.